Sensorimotor cortex activity during basketball dribbling and its relation to creativity. - Thomas Kanatschnig; Christian Rominger; Andreas Fink; Guilherme Wood; Silvia Erika Kober (PLoS ONE, 2023)
Previous studies suggest that it is possible to influence creative performance, by increasing the level of activity in one of the brains hemispheres through unilateral hand movements. Stronger right-hemispheric brain activation due to left-hand movement is assumed to promote creative performance. In this study the aim was to replicate these effects and to expand previous findings, by incorporating a more advanced motor task. 43 right-handed participants were asked to dribble a basketball with the right (n = 22) or left hand (n = 21), respectively. During dribbling the brain activity was monitored over the sensorimotor cortex bilaterally using functional near-infrared spectroscopy (fNIRS). By investigating two groups (left-hand dribbling vs. right-hand dribbling) and by conducting a pre-/posttest design for measuring creative performance (verbal as well as figural divergent thinking tasks), effects of both left- and right-hemispheric activation on creative performance were examined. The results show that creative performance could not be modulated through basketball dribbling. Yet the analysis of the brain activation patterns in the sensorimotor cortex during dribbling revealed findings that largely correspond to the results on hemispherical activation differences during complex motor tasks. Higher cortical activation in the left hemisphere, relative to the right hemisphere, during right-hand dribbling, as well as higher bilateral cortical activation during left-hand dribbling, compared to right-hand dribbling was observed. The results of a linear discriminant analysis further revealed that high group classification accuracy could be achieved using sensorimotor activity data. While we were not able to replicate effects of unilateral hand movements on creative performance, our results reveal new insights into the functioning of sensorimotor brain regions during advanced movement.